Proportional Resonant Controller-Based Virtual Powerplant with improved Dynamic Response in Distribution Network (Journal of Scientific Research, 2025)
The concept of Virtual Power Plant (VPP) emerges as a pivotal advancement in power systems engineering, aiming to enhance the integration of renewable energy sources into the power market. This research delves into the challenges faced by Distributed Energy Resources (DERs), such as power losses, voltage variations, and revenue losses in the distribution network, hindering the effective participation of small-scale renewable energy sources in the power market. Furthermore, the research addresses the challenge of poor dynamic response in VPPs attributed to dynamic loads and DER characteristics. To mitigate this, a Proportional Resonant (PR) controller is proposed to enhance the dynamic performance of the VPP. Comparative analysis with the conventional Fractional Order Proportional Integral Derivative (FOPID) controller reveals the superiority of the PR controller. The PR-controlled VPP exhibits improved dynamic performance with a lower settling time of 0.49 seconds and a reduced steady-state error of 2.78 compared to the FOPID controller. The investigations extend to the comparison of voltage, real power, and reactive power between the FOPID and PR controllers. The results underscore the superior response of the PR-controlled VPP, showcasing its efficacy in achieving faster responses and minimizing spikes in voltage and power variables.